Physiological responses during exercise performed to exhaustion at critical power - Baron, B.; Dekerle, J.; Robin, S.; Neviere, R.; Dupont, L.; Matran, R.; Vanvelcenaher, J.; Robin, H.; Pelayo, P. (Journal of Human Movement Studies, 2005)
The aim of this study was to examine the response of physiological parameters during exercise to exhaustion at Critical Power (CP). Eight male trained subjects performed a test to exhaustion on a cycle ergometer at a constant power corresponding to their previously determined CP. Mean CP value was 283.6±20W and corresponded to 85.4±4.8% of VO2 max. Time to exhaustion was 22.1±10.1min and was associated with a pattern in lactate concentration, redox state, ammonia concentration, minute ventilation, respiratory rate, heart rate. Likewise, a decrease of [HCO3-, ], PaCO2 and base excess was observed between the 10th min and the end of the test, associated with an acidosis which cannot be compensated. The rise in these parameters could lead to exhaustion and the inability to maintain the exercise intensity. VO2 did not change after the 10th min of the test but was higher than the level expected for this intensity, due to a VO2 slow component though VO2 max level was not attained. These results demonstrated that CP does not correspond to a sustainable and physiological steady state intensity.